2013
DOI: 10.1080/08854726.2013.775820
|View full text |Cite
|
Sign up to set email alerts
|

Chaplaincy and Mental Health in the Department of Veterans Affairs and Department of Defense

Abstract: Chaplains play important roles in caring for Veterans and Service members with mental health problems. As part of the Department of Veterans Affairs (VA) and Department of Defense (DoD) Integrated Mental Health Strategy, we used a sequential approach to examining intersections between chaplaincy and mental health by gathering and building upon: (1) input from key subject matter experts; (2) quantitative data from the VA/DoD Chaplain Survey (N = 2,163; response rate of 75% in VA and 60% in DoD); and (3) qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 23 publications
2
69
0
Order By: Relevance
“…Findings from the survey and site visits suggest that while VA chaplains, DoD healthcare chaplains, and DoD non-healthcare chaplains are distinct in a number of ways, chaplains from both departments frequently care for veterans and service members with mental health needs 21 and can function as important members of integrated care teams. Survey results indicate that when VA and DoD chaplains serve as members of integrated healthcare teams, they overwhelmingly feel that their role is understood and valued by the rest of the team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the survey and site visits suggest that while VA chaplains, DoD healthcare chaplains, and DoD non-healthcare chaplains are distinct in a number of ways, chaplains from both departments frequently care for veterans and service members with mental health needs 21 and can function as important members of integrated care teams. Survey results indicate that when VA and DoD chaplains serve as members of integrated healthcare teams, they overwhelmingly feel that their role is understood and valued by the rest of the team.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the military where fears persist about mental health treatment potentially leading to negative career repercussions or perceptions that one is weak, chaplains are often considered a safer, trusted, and more confidential option. 21,22 Veterans and service members may also seek out chaplains because chaplains are able to address salient spiritual dynamics related to depression, posttraumatic stress disorder (PTSD), and other common psychiatric problems. For instance, research suggests that PTSD severity, chronicity, and treatment seeking are often interwoven with issues of guilt, 23,24 forgiveness, 25,26 religious faith, [27][28][29] meaning and purpose, 27,30 and moral injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although not included in this systematic review, the authors believe the work conducted by Nieuwsma et al 65,66 in the Veterans Affairs (VA) and Department of Defense (DoD) also deserves mention. Nieuwsma and colleagues studied and increased the integration of PaC and mental health services in the VA and DoD.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that VA and DoD chaplains commonly saw patients with mental health issues and that increased integration had the benefits of reducing stigma associated with receiving mental health care and increasing access to this care. 65 They concluded that strategies to increase interaction between PaC providers and mental health care providers (eg, joint clinical rounds), joint training of PaC providers and mental health care providers, and other recommended strategies would greatly improve integration of the 2 disciplines. 65 They reported that PaC providers often felt that mental health care providers did not understand the chaplains' role and that this led to decreased integration of the 2 teams, 65 but that, when PaC providers were included in interdisciplinary mental health care teams, they felt understood and validated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that chaplains play a key role in suicide prevention among active-duty soldiers [41]. In a 2013 study, Nieuwsma and colleagues found that 65% of DoD chaplains believed that active-duty service members who sought chaplaincy services did so because of concerns about confidentiality in traditional mental health settings [42].…”
Section: Department Of Defense Programsmentioning
confidence: 99%